2019
DOI: 10.1016/j.jpainsymman.2018.12.332
|View full text |Cite|
|
Sign up to set email alerts
|

Attitudes of the General Public, Cancer Patients, Family Caregivers, and Physicians Toward Advance Care Planning: A Nationwide Survey Before the Enforcement of the Life-Sustaining Treatment Decision-Making Act

Abstract: Context. To respect a patient's wish for end-of-life care, ''the Act on Decisions on Life-Sustaining Treatment for Patients at the End-of-Life'' was enacted in South Korea in 2016. Current understanding of people who would be involved in advance care planning (ACP) is crucial to disseminate it systematically. Objectives. The objective of this study was to investigate awareness and attitudes toward ACP in South Korea. Methods. A multicenter, nationwide cross-sectional study was conducted a survey regarding ACP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 25 publications
(22 reference statements)
2
32
0
Order By: Relevance
“…In a study before the law was enacted, it reported the findings on whether life-sustaining treatment decision forms could be applied in the actual oncological practice. An Korea reported that a total of 15% of the general population, 33% of the patients and caregivers, and 61% of the physicians had knowledge of advance directives [11]. From these results, Koreans lacked awareness regarding the process of discussing medical care and determining life-sustaining treatment at the end-of-life.…”
Section: Discussionmentioning
confidence: 99%
“…In a study before the law was enacted, it reported the findings on whether life-sustaining treatment decision forms could be applied in the actual oncological practice. An Korea reported that a total of 15% of the general population, 33% of the patients and caregivers, and 61% of the physicians had knowledge of advance directives [11]. From these results, Koreans lacked awareness regarding the process of discussing medical care and determining life-sustaining treatment at the end-of-life.…”
Section: Discussionmentioning
confidence: 99%
“…In Korea, physicians tend to avoid telling the truth to patients directly, concerned that they might be frightened or depressed, so family caregivers are frequently surrogate decision-makers, and do not always respect the patient’s will [ 11 ]. However, patients want to know their disease status [ 16 ] and discuss ACP in person [ 17 ]. Not considering patient’s own values, wishes, and goals may result in unnecessary LSTs [ 18 ] and deteriorate quality of life for patients and caregivers [ 4 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in Korea, DNR orders are usually written in a week before dying [ 7 , 9 , 15 ], which means that most of them are documented without proper ACP. To be more effective, we should consider initiating ACP discussion when a patient is diagnosed with critical or terminal illness [ 17 , 26 ]. However, short outpatient consultation time [ 27 ], communication difficulties [ 26 ], or patients' inaccurate understanding of illness [ 1 , 28 ] may hinder early initiation of ACP.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study on intensive care unit doctors in Asia reported that among the factors that these doctors considered to be important in making LSTrelated decisions, the needs of the family accounted for 77.9%; it was only surpassed by the factors patient's intention (84.1%) and long-term quality of life [3]. It is well-established fact that the physician's perception of the intention of the family and the preference of the patient may sometimes be different than the patient's original intention [1,20,21]. Personal characteristics or experience of the physician could also influence LST-related decisions, which inherently presents the risk of a decision being made contrary to the patient's intention [11].…”
Section: Discussionmentioning
confidence: 99%
“…Considering that one in three US adults files any type of advance statement on LST [17], longterm policies for increasing the completion rate of advance statement on LST among adults aged ≄19 years are needed in Asia, including South Korea [20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%